Journal Writing as a Developmental Guidance Method - Buttery, John; Allan, John A. B. (Canadian Journal of Counselling and Psychotherapy, 2012)
Students in a regular Grade 7 class participated in a developmental guidance program that was designed around writing two journal enteries a week for the school year. The program was included in the Language Arts curriculum and was seen as a natural part of school life. The students used the program to write about their own individual tasks and issues. Seven key journal themes were identified that reflected concern over parents, siblings, career aspirations, national and international issues, emotions, and philosophical and reli- gious themes. The writing process and class discussions which followed seemed to facilitate emotional, social, and academic growth, to improve the classroom climate, and to increase the communication flow between students, teacher, and parents.